290OLong-term results of phase II trial of reduced modified clinical target volume in low-risk nasopharyngeal carcinoma treated with intensity modulated radiotherapy. (24th November 2019) - Miao, J; Di, M; Cao, Y; Wang, L; Xiao, W; Zhu, M; Chen, B; Huang, S; Han, F; Deng, X; Xiang, Y; Chua, M L K; et al.
Abstract: Background: Intensity modulated radiation therapy (IMRT) is the standard of care for nasopharyngeal carcinoma (NPC). Part of the IMRT quality assurance process involves accurate target volume delineation, which is crucial for local control and survival. Current practice utilizes a uniform contouring method for clinical target volume (CTV) for all stages of NPC. Here, we conducted a single-arm phase 2 trial investigating the tumor control rates of reduced CTV margins and corresponding doses in low-risk, early-stage NPC. Methods: Patients with biopsy-proven stage I-IIb (6th UICC/AJCC) NPC were enrolled. All patients were treated with IMRT alone. Two CTVs (CTV1 [high risk] and CTV2 [low risk]) were outlined; CTV1 was defined by grossly identified tumour (on MRI or CT) plus 5-mm margin (3-mm posteriorly); CTV2 was CTV1 plus 5-mm margin (3-mm posteriorly). 60 Gy and 50–54 Gy in 30 fractions were prescribed to CTV1 and CTV2, respectively. Primary end-point was locoregional recurrence free survival (LRRFS). Results: From May 2001 to August 2006, 103 patients were recruited; all patients completed IMRT as planned (time duration 39-61 days). At a median follow-up of 12.6 years, five patients developed locoregional failures; of which one was in-field, and four were regional recurrence (two in-field and two marginal). 10-year LRRFS, distant metastasis free survival (DMFS), disease specific survival (DSS) and overall survival (OS) were 95.0% and 94.1%, 94.0% and 91.1%, respectively. The most common grade 1-2 late toxicities included subcutaneous fibrosis (79.6%), hearing loss (53.4%) and skin dystrophy (43.2%); grade 3 included subcutaneous fibrosis (2.9%) and hearing loss (2.9%); and no grade 4 late toxicity. Conclusions: Reduced CTV margins and corresponding doses results in optimal longterm tumour control, with minimal late adverse events. Clinical trial identification: NCT03839602. Legal entity responsible for the study: Prof. Chong Zhao. Funding: Has not received any funding. Disclosure: M.L.K. Chua: Honoraria (self), Advisory / Consultancy: Janssen, Astellas, Varian, Ferring Singapore and AstraZeneca; Research grant / Funding (institution): Ferring Singapore, GenomeDx Biosciences, Varian, MedLever. All other authors have declared no conflicts of interest.